Hydraulic conductivity from the Mendaram peat swamp in Brunei Darussalam - Alexander R Cobb; Charles Franklin Harvey (PANGAEA, 2019)
The hydraulic conductivity knots are recorded along with their 95% confidence intervals. Details on how they were computed from the peat surface Laplacian and throughfall and water table time series are provided in Cobb and Harvey (2019).
In supplement to: Cobb, AR; Harvey, CF (2019): Scalar Simulation and Parameterization of Water Table Dynamics in Tropical Peatlands. Water Resources Research, 55(11), 9351-9377, https://doi.org/10.1029/2019WR025411